2001
DOI: 10.1055/s-2001-19011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiopulmonary Bypass on Myocardial Function, Damage and Inflammation after Cardiac Surgery in Newborns and Children

Abstract: In summary, perioperative measurement of cTnI, CK and PCT reflects myocardial damage and systemic inflammatory response and allows an improved peri- and postoperative management. PiCCO technique is an excellent, less invasive tool to determine postoperative cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Monitoring the cardiac output by means of femoral artery thermodilution (PiCCO) is a less invasive technique that requires only catheterization of the femoral artery and a central venous catheter (2,3). This technique may be used in children of any age, including neonates (3,4). A number of studies have shown that a good correlation exists between the output measured by pulmonary artery and femoral artery thermodilution (3)(4)(5).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Monitoring the cardiac output by means of femoral artery thermodilution (PiCCO) is a less invasive technique that requires only catheterization of the femoral artery and a central venous catheter (2,3). This technique may be used in children of any age, including neonates (3,4). A number of studies have shown that a good correlation exists between the output measured by pulmonary artery and femoral artery thermodilution (3)(4)(5).…”
mentioning
confidence: 98%
“…This technique may be used in children of any age, including neonates (3,4). A number of studies have shown that a good correlation exists between the output measured by pulmonary artery and femoral artery thermodilution (3)(4)(5).…”
mentioning
confidence: 98%
“…Liet [9] previously used PiCCO2 monitoring in rabbits and other small animals [13]. The pulse-contour algorithm was also used to evaluate CO in a pediatric population, including newborns undergoing cardiac surgery [14]. PiCCO2 monitoring was appropriately calibrated for pulse contour analysis at every measurement time point using two 3-mL bolus injections of 4 C normal saline.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…Elevated cardiac troponin is a specific marker for myocardial damage for both adults and children. 1 Biochemical markers for ischemia have not been routinely used in children at risk for myocardial damage. It is generally believed that elevation of these markers is extremely uncommon in children, especially in infants.…”
mentioning
confidence: 99%